Effect of erosive challenge and cigarette smoke on dentin microhardness, surface morphology and bond strength - Ferretti, Marcela Alvarez; Theobaldo, Jéssica Dias; Pereira, Renata; Vieira-Junior, Waldemir Francisco; Ambrosano, Glaucia Maria Bovi; Aguiar, Flávio Henrique Baggio (Brazilian Dental Science, 2020)
Objective: This study aimed to evaluate the surface microhardness and morphology, as well as the microshear bond strength of a self-etching adhesive (Clearfil SE, Kuraray) to eroded dentin, exposed or not to cigarette smoke. Forty dental crowns were divided into 4 groups (n = 10): no treatment (control) (C); erosion (E); erosion + cigarette smoke exposure (ES); cigarette smoke exposure (S). Samples were prepared through third molars polishing until dentin exposure, followed by crown section. Erosive cycles were performed 5 times/day for 30 s at 60 min intervals. Cigarette smoke was produced with twenty cigarettes/day, during 5 days. Microhardness was evaluated initially and after the treatments. Microshear bond strength was tested after the treatments and dentin restoration with flow composite. Failure patterns and dentin morphology was evaluated by Scanning Electron Microscopy. Microshear bond strength data was submitted to two-way ANOVA, microharness test was adjusted by gamma distribution to be a non-parametric analyses (p=0.05), and surface morphology as qualitative analyses. Loss percentage of microhardness was observed only in groups submitted to erosion. Bond strength was statistically similar between all groups. The most prevalent failure pattern was of adhesive type. Morphological analysis of dentin showed obliterated tubules in groups submitted to cigarette smoke exposure. Cigarette smoke exposure did not promote any effect in the percentage of microhardness loss, as in sound dentin as in eroded dentin. Cigarette smoke, erosion, and association of both, did not alter the bond strength of self-etching adhesives to dentin. Keywords Bond strength; Cigarette Smoke; Dental erosion; Microhardness; Self-etching adhesives.